2011
DOI: 10.1177/1046496411399782
|View full text |Cite
|
Sign up to set email alerts
|

Communication, Performance, and Perceptions in Experimental Simulations of Resource Dilemmas

Abstract: The response of groups to the experience of coping with resource dilemmas has been an object of study by scholars in several of the social and behavioral sciences. Social norms, trust, and the perception of group identity form cooperative mechanisms critical to group cooperation. However, the opportunity to communicate has been singled out as the most important factor influencing group cooperation performance in resource dilemmas. Until recently, the content of that communication has undergone little examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The development of the category scheme, described in previous papers (Pavitt, ), consisted of an inductive process based on the discussion of five pilot sessions. It includes two codes for each unit (see Table ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The development of the category scheme, described in previous papers (Pavitt, ), consisted of an inductive process based on the discussion of five pilot sessions. It includes two codes for each unit (see Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, however, the content of that communication has undergone no more than cursory examination. The study reported herein is the fourth in a series of experimental simulations intended to close that research gap (see Pavitt, , for summary and relevant references). In each of the previous three, the specific goal was to take an input variable with known impact on pool maintenance success and examine the process that is likely responsible for that impact.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the underlying causal processes are still debated, it is well known that communication improves outcomes in social dilemmas (Ostrom et al 1992, Sally 1995. Previous studies have concluded that it is the option for and the amount of communication rather than the content of the communication that is necessary to improve outcomes (Pavitt et al 2005, Janssen 2010, but see Pavitt 2011). We analyzed communication by linking the content of the communication among participants to social roles.…”
Section: Introductionmentioning
confidence: 99%